Effect of tibolone and raloxifene on serum markers of apoptosis in postmenopausal women. (April 2013) - Lambrinoudaki, I.; Karaflou, M.; Kaparos, G.; Alexandrou, A.; Creatsa, M.; Aravantinos, L.; Augoulea, A.; Kouskouni, E.
ABSTRACT Objectives To investigate the effect of tibolone and raloxifene on the serum apoptotic markers soluble Fas (sFas), soluble Fas ligand (sFasL) and cytochrome-c (cyt-c) in postmenopausal women. Methods A total of 89 healthy postmenopausal women, attending the University Menopause Clinic, were randomly allocated to tibolone (n =30), raloxifene (n =29) or no treatment (n =30). Serum apoptotic markers sFas, sFasL and cyt-c were measured at baseline and at 6 months. Results Serum sFasL decreased significantly in women receiving tibolone (baseline: 53.8±28.3 pg/ml, 6 months: 40.45±19.2 pg/ml, p =0.001), whilst sFas levels did not significantly change in this group. Serum sFas or sFasL did not change either in the raloxifene group or in the control group. Serum cyt-c concentrations were under the detection limit of the assay in all women assessed. Conclusions Tibolone use resulted in a significant decrease in serum sFasL, but not in serum sFas. Raloxifene had no effect on either sFas or sFasL. These results may indicate that tibolone use is associated with a decrease in receptor-mediated apoptosis.